Road User Charging: Financing the Future of Transportation - Venkateswarlu Mullangi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the evolution, implementation challenges, and future potential of Road User Charging (RUC) systems as an alternative transportation infrastructure funding mechanism. The article investigates how declining fuel tax revenues and increasing vehicle efficiency have created a critical need for sustainable funding solutions. Through a detailed examination of pilot programs, technical infrastructure requirements, and institutional frameworks, the research demonstrates RUC's viability as a replacement for traditional funding methods. The article explores integration opportunities with connected and automated vehicles, highlighting potential improvements in revenue generation, system efficiency, and user acceptance. Additionally, the study addresses key implementation challenges and provides recommendations for policy development, technical deployment, and ongoing system monitoring, offering insights into establishing successful RUC programs that ensure equitable and sustainable transportation infrastructure funding.
Keywords: Road User Charging; Infrastructure Funding; Transportation Technology; Connected Vehicles; Revenue Sustainability